Physicochemical and Sensory Properties of Wine Produced from Blended Cactus Pear (Opuntia ficus-indica) and Lantana camara (L. camara) Fruits - Zenebe Tadesse Tsegay; Kidu Mezgebe Gebremedhin (Journal of Food Quality)
Blending different fruits as well as adding medicinal herbs improves important physicochemical and sensorial properties of fruit wine. The present study aimed at investigating prominent physicochemical and sensory properties of wine produced from cactus pear and Lantana camara fruit juice blend. Both fruit juices were characterized based on pH, sugar, titratable acidity, total phenol, and organic acid contents. The fermentation process was made at previously optimized fermentation temperature of 24.8°C, pH of 3.4, inoculum concentration (Saccharomyces cerevisiae) of 10.16% (v/v), and Lantana camara fruit juice concentration of 10.66% (v/v). The final wine was characterized as having pH of 3.47 ± 0.04, 4.6 ± 0.02 g/L sugar equivalent to dextrose, 0.33 ± 0.006% titratable acidity (w/v citric acid), total phenol of 696.1 ± 22.1 mg/L equivalent to gallic acid, and 4.35 ± 0.4 mg/mL organic acid equivalent to citric acid composition. Predominant color intensity, ethanol, methanol, total sulfite, and sensory value of the final wine were measured as 48.07 ± 2.66% of yellowish color, 8.6 ± 0.68% (v/v), 124.4 ± 9.5 mg/L, 129.94 ± 4.04 mg/L, and 8.65 ± 0.92, respectively. The blended Lantana camara fruit enhanced total phenol, color, and sensory value of the final wine. Titratable acidity and methanol and sulfite contents of the final wine are in an acceptable limit compared to standards for commercial wines. Utilizing cactus pear fruit by incorporating Lantana camara fruit for health-enhancing functional food development such as fruit wines could solve the current postharvest loss of both fruits and be a means of alternative beverage.